ON - Nazar H. Shuker; Dina A. Basheer; Shaimaa S. Esa (QALAAI ZANIST SCIENTIFIC JOURNAL, 2018)
In this paper we investigate the SF-rings over γregular rings and the relations between them. Moreover, we impose some conditions to obtain an interesting property of SSF-rings over γ-regular rings.